DISTRIBUTION OF CORAL COMMUNITIES ON REEF SLOPES IN THE MASCARENE ARCHIPELAGO, INDIAN OCEAN - Faure, Gerald (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1977)
Three zones and sic